Air pollution control equipment calculations. - Theodore, Louis, 1934- (Hoboken : Wiley, 2008)
This book's problem-and-solution approach enables readers to quickly grasp the fundamentals of air pollution control equipment and essential applications. Moreover, the author sets forth solid principles for the design and selection of air pollution control equipment as well as for its efficient operation and maintenance. Readers gain a deep understanding of both the equipment itself and the many factors affecting performance. Following two introductory chapters, the book dedicates four chapters to examining control equipment for gaseous pollutants, including adsorption, absorption, and incineration equipment. The remaining six chapters deal with equipment for managing airborne particulate pollutants, including gravity settlers, cyclones, electrostatic precipitators, scrubbers, and baghouses. The appendix contains discussions of hybrid systems, the SI system (including conversion constants), and a cost-equipment model. Each chapter offers a short introduction to the control device discussed. Next, progressively more difficult problems with accompanying solutions enable readers to build their knowledge as they advance through the chapter. Problems reflect the most recent developments in pollution control and include a variety of performance equations and operation and maintenance calculations. Each problem includes a statement of the problem, the data used to solve the problem, and a detailed solution. Readers may further hone their skills by visiting the text's Web site for additional problems and solutions. This publication serves both as a textbook for engineering students and as a reference for engineers and technicians who need to ensure that air pollution control equipment operates efficiently and enables their facility to meet all air pollution control standards and regulations.